2017
DOI: 10.7717/peerj-cs.134
|View full text |Cite
|
Sign up to set email alerts
|

The appropriation of GitHub for curation

Abstract: GitHub is a widely used online collaborative software development environment. In this paper, we describe curation projects as a new category of GitHub project that collects, evaluates, and preserves resources for software developers. We investigate:(1) what motivates software developers to curate resources; (2) why curation has occurred on GitHub; (3) how curated resources are used by software developers; and (4) how the GitHub platform could better support these practices. We conduct indepth interviews with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Distill uses GitHub for transparent peer review and post-publication peer review [84]. GitHub is increasingly used for resource curation [85], and collaborative scholarly reviews combine literature curation with discussion and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Distill uses GitHub for transparent peer review and post-publication peer review [84]. GitHub is increasingly used for resource curation [85], and collaborative scholarly reviews combine literature curation with discussion and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Other very strong motivations for sharing are enjoyment and being creative while contributing to software development. Another study [17] showed that software developers have intrinsic and extrinsic motivations. According to their study the main intrinsic motivation is altruism; the main extrinsic motivations are personal needs (e.g., efficient learning tools, communication with the community) and peer recognition.…”
Section: Code Sharing: Reasons For Sharingmentioning
confidence: 99%
“…Prior literature has documented software practices on GitHub well [1,2,8], and some literature has provided insights into the curator's motivations and the users' experiences with curation repositories [3,4]. However, a gap still exists in how GitHub features are utilized in curation repositories and how they are adopted differently, as compared to the intended software practice.…”
Section: Rq2: What Is the Emerging Role Of Curation Repositories In Tmentioning
confidence: 99%
“…Studies of this phenomenon have investigated the motivations of curators and user experiences with curation repositories [3,4]. The analysis of GitHub features for supporting curation, as well as the role that curation repositories have been playing in the software developers' community, are still missing.…”
Section: Introductionmentioning
confidence: 99%